The common transport policy of the EEC - Charles C. McKay (Intereconomics, 1987)
A free market in the sphere of transport is to be established in the European Community by 1992. What conditions prevail today in this sector and what steps must be taken in order to establish a workable Common Transport Market?
Keywords: 330; Transportation